“The internet is slow!”: building a context-oriented learning management system - Ramos, Rita Cui; Garcia, Primo; Roxas-Ridulme, Queenie; Cabanes, Ria Valerie; Rosario, Hanna May; Enrile, Marie Karen; De Jesus, Ronaldo (Institute of Advanced Engineering and Science, 2024)
In this study, researchers analyzed the current distance learning situation in the Philippines as part of a four-phase project to create a Filipinized learning management system (LMS) for nursing students and educators. A mixed-methods approach was utilized by conducting 17 online focus group discussions (FGDs) in selected nursing universities from the Philippines and disseminating an online survey with a sample size of 80 nursing educators and student participants. Results revealed that both nursing students and educators faced barriers in their online learning and teaching experiences and in using LMS. Educators showed how slow internet connections and power outages, lack of training with the use of technology and LMS, lack of technology resources, and lower student engagement hampered the delivery of learning. Students also shared problems with instability of internet connection, teacher-student and student-student communication, and learning environment. Both teachers and students also recognized time efficiency, cost-effectiveness, the accessibility of learning materials, and flexibility in learning as benefits of online learning. The study provided an in-depth understanding of the situation of Filipino online nursing students and educators that may be used in developing the Filipinized LMS and in building educational policies and programs for online learning